Distribution of Chlorophil-A and Sea Surface Temperature (SST) on Operation of Payang Catching Equipment in Gorontalo Bay Waters - Asruddin Asruddin; Ady Jufri; Mohamad Sayuti Djau (Journal La Multiapp, 2022)
This research was carried out in January - August 2020 with the aim of looking at the temporal and spatial distribution of Chlorophyll-a (CHL-a) and Sea Surface Temperature (SST) in the waters of Gorontalo Bay, their effect on payang catches. The data used in the form of field data and image data were analyzed by descriptive analysis and analysis of Geographic Information Systems (GIS). Based on the results of the study, it was found that the existence of payang fishing gear in Gorontalo Bay is in an area that has a high chlorophyll content between the West Season, West-East Transition Season and East Season. The highest average payang catch was found in the West-East transition season compared to other seasons. The West-East transition season has sea surface temperatures between 30.64°C-30.99°C while the density of chlorophyll-a is 0.1701 mg/m3-0.1925 mg/m3.